Resilience building interventions to manage climate induced livestock poverty and deaths in Southern Zimbabwe - Rameck Defe; Mark Matsa; Takunda Shabani (Nature-Based Solutions)
Livestock production in Mwenezi District (MD) has become more susceptible to effects of climatic variability and change which undermines developmental gains from livestock value chain. Climate change impacts are increasing the intensity of livestock poverty and deaths across all forms of livestock. The study examined livestock production interventions implemented to reduce livestock poverty deaths in MD. Descriptive research design which utilizes both qualitative and quantitative paradigms was used to accurately and systematically describe the phenomenon. A household survey questionnaire was administered to sampled households in MD wards 4 and 10 while interviews were conducted with purposively selected key informants from the department Agriculture Technical and Extension Services (AGRITEX), Veterinary Services Department, Rural District Council, CARE and District Development Coordinator's Office. Various interventions including construction of improved livestock structures, availing of safe drinking water for livestock, livestock feed formulation have been initiated to reduce and contain livestock poverty deaths. The study recommends that development actors should initiate more interventions to boost livestock production sector since it is the most suitable intervention in relation to climate and weather conditions experienced in MD. The research offers insights to address the complex interplay between climate change, livestock farming, poverty and resilience building. Results inform future researchers while guiding policy makers working in similar contexts on how best to support vulnerable communities. Findings lessen the burden to achieve Sustainable Development Goals namely no poverty, zero hunger amongst others. The study enlightened farmers on how to implement drought mitigation and adaptation techniques during drought periods.